2008
DOI: 10.3989/gya.064408
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Lactobacillus plantarum strains for their use as starter cultures in Algerian olive fermentations

Abstract: RESUMENSelección de cepas de Lactobacillus plantarum para su uso como cultivos iniciadores en la fermentación de aceitunas de Argelia.El objetivo de esta investigación fue evaluar algunos aspectos tecnológicos de cepas de L. plantarum previamente aisladas de aceitunas fermentadas. Para este propósito, 11 cepas fueron usadas para estudiar su susceptibilidad a antibióticos in vitro, resistencia a valores de pH bajos, actividad acidificante, proteolítica, y hemolítica, producción de ácido láctico y exopolisacárid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Thus, several studies have been conducted to assess the probiotic effects of strains isolated from different fermented olives cultivars and/or already used as starter cultures, belonging to the most widely spread species L. plantarum and L. pentosus, as well as to species less frequently used, such as L. paracasei, L. casei, and L. paraplantarum [43,85,[100][101][102][103][104][105][106]. Some studies revealed that some LAB strains isolated from table olives were able to adhere to porcine jejune epithelial cells IPEC-J2 and produced antimicrobial compounds able to inhibit Helicobacter pylori, Propionibacterium spp., and Clostridium perfringens [10,70,[107][108][109]. Probiotic potential, based on the ability to outcompete foodborne pathogens for cell adhesion, was also characterized in several L. pentosus isolated from different table olive cultivars (i.e., Nocellara del Belice and Aloreña green table olives) [103,110].…”
Section: New Trend In Olive Production: Probiotic Table Olivesmentioning
confidence: 99%
“…Thus, several studies have been conducted to assess the probiotic effects of strains isolated from different fermented olives cultivars and/or already used as starter cultures, belonging to the most widely spread species L. plantarum and L. pentosus, as well as to species less frequently used, such as L. paracasei, L. casei, and L. paraplantarum [43,85,[100][101][102][103][104][105][106]. Some studies revealed that some LAB strains isolated from table olives were able to adhere to porcine jejune epithelial cells IPEC-J2 and produced antimicrobial compounds able to inhibit Helicobacter pylori, Propionibacterium spp., and Clostridium perfringens [10,70,[107][108][109]. Probiotic potential, based on the ability to outcompete foodborne pathogens for cell adhesion, was also characterized in several L. pentosus isolated from different table olive cultivars (i.e., Nocellara del Belice and Aloreña green table olives) [103,110].…”
Section: New Trend In Olive Production: Probiotic Table Olivesmentioning
confidence: 99%